Film processing advances - Kanai, Toshitaka, 1952-; Campbell, G. A. (Hanser Publishers ; Hanser Publications, 2014)
"This volume deals with manufacturing processes for preparing very thin polymer products"--Resumé vydavatele
Keywords: polymerní filmy; plastové fólie; zpracování plastů; polymer films; plastic foils; plastics processing; kolektivní monografie; collective monographs